1998
DOI: 10.1097/00001888-199803000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Are medical students ready to provide HIV-prevention counseling?

Abstract: A majority of experienced medical students did not assess several important risk factors of a patient concerned about HIV infection, and many would have provided incorrect information related to HIV testing and prevention of infection. Patient contact in traditional clinical settings did not influence prevention knowledge or behavior. More innovative methods are needed to train students in HIV-infection prevention and counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…67 In practice, although students often ask patients basic questions on safer sex practices, some reports have suggested that inquiry on STI history and specific sexual practices is lacking. 68 The public health importance of STI education has ensured that this topic is generally well covered in most medical schools; a 2008 study reported that more than 90% of surveyed U.S. medical students reported some or extensive training in discussing safer sex with patients. Despite this finding, almost half the clinical students reported that they were only "somewhat" confident in discussing safer sex with patients and only 17% engaged in this discussion "always."…”
Section: Sexually Transmitted Infections and Hivmentioning
confidence: 99%
“…67 In practice, although students often ask patients basic questions on safer sex practices, some reports have suggested that inquiry on STI history and specific sexual practices is lacking. 68 The public health importance of STI education has ensured that this topic is generally well covered in most medical schools; a 2008 study reported that more than 90% of surveyed U.S. medical students reported some or extensive training in discussing safer sex with patients. Despite this finding, almost half the clinical students reported that they were only "somewhat" confident in discussing safer sex with patients and only 17% engaged in this discussion "always."…”
Section: Sexually Transmitted Infections and Hivmentioning
confidence: 99%
“…3 Lecture was the most common format. Despite this, studies of medical students, 4 residents, 5 and physicians continue to show a lack of adequate sexual history taking due to inability to identify at-risk populations or behaviors, 6 perceived irrelevance 7 of sexual health inquiry, and discomfort in approaching such a personal and sensitive subject. 8,9 Consequently, the curricula of residency programs and medical schools have been adjusted to address these inadequacies.…”
Section: A Student-designed and Student-led Sexual-historytaking Modumentioning
confidence: 99%
“…8,9 Consequently, the curricula of residency programs and medical schools have been adjusted to address these inadequacies. 4,5,[10][11][12] Sex and sexual practices are an important aspect of health for all patients. Physicians need the appropriate skills to ask sensitive questions that are nonjudgmental and empathetic.…”
Section: A Student-designed and Student-led Sexual-historytaking Modumentioning
confidence: 99%
“…Studies of medical students, residents, and practicing physicians have documented that HIV risk behavior continues to go unidentified, and that counseling on HIV prevention is ineffective (Curtis et al 1994;Cook et al 1998;Liddicoat et al 2004). A survey of British medical graduates found that less than 45% felt that they could conduct an appropriate HIV pre-test discussion, and less than 60% felt that they could recognize clinical indicators suggestive of HIV (Estcourt et al 2009).…”
Section: Introductionmentioning
confidence: 99%